Prevalence and risk factors of hypertension in HIV-positive adults on antiretroviral therapy in Ondo State, Nigeria (2020)
Abstract Introduction: The occurrence of hypertension in people living with human immunodeficiency virus/ acquired immunodeficiency syndrome (PLWHA) on antiretroviral therapy (ART) is increasing. In Nigeria, where the national human immunodeficiency virus (HIV) prevalence is 1.4%, an estimated 700,000 PLWHA are on ART. We investigated the prevalence of hypertension and associated factors among adults on ART in Owo, Ondo State Material and methods: A retrospective study with 300 PLWHA on ART in Federal Medical Centre, Owo, was conducted. Hypertension was defined as systolic blood pressure (SBP) ≥ 140 mm Hg and/or diastolic blood pressure (DBP) ≥ 90 mm Hg. Descriptive statistics were performed. Chi-square tests were used to identify associations between sociodemographic/clinical parameters and hypertension. Odds ratio and adjusted odds ratio were used to examine risk factors associated with hypertension. Results: The mean age of PLWHA was 38.3 years (SD, 10.4) and 33.7% were males. Median duration on ART was 6 years (range, 0.5-15). The prevalence of hypertension was 20.3%, with 25.7% in males and 17.5% among females. The prevalence of hypertension before commencing ART was 14.7% and 20.3% after ART was commenced (p = 0.043). Mean SBP was 110 ± 16 mm Hg before ART use and 118 ± 18 after utilization of ART (p < 0.001). Hypertension before commencing ART was associated with age of 38 years and above (OR: 2.7; 95% CI: 1.3-6.8). Amongst PLWHA, hypertension after com mencing treatment was associated with being previously hypertensive (AOR: 9.2; 95% CI: 4.5-18.6). Conclusions: HIV treatment programs should include screening and management of hypertension. Screening and assessment of risk factors were directed at PLWHA diagnosed with hypertension before commencing ART, while routine check of blood pressure was evaluated at subsequent visits. HIV AIDS Rev 2020; 19, 3: 199-205 DOI: https://doi.org/10.5114/hivar.2020.99681 Key words: HIV, anti-retroviral therapy, PLWHA, hypertension among PLWHA.